Individual responsibilities, collective issues: The framing of dietary practices in Latvian media. (1st September 2021) - Orste, Lina; Krumina, Alise; Kilis, Emils; Adamsone-Fiskovica, Anda; Grivins, Mikelis
Abstract: Topics concerning food and diets have gained prominence in academic writing, policy debates and media coverage, not least due to public health problems, sedentary lifestyles, and concerns regarding dietary habits and the impact of food production on climate change. The purpose of this paper is to reveal the ways dietary practices have been framed in the media through an analysis of Latvian print and digital media articles. A selection of 192 media articles published between 2014 and 2019 were analysed through the perspective of framing. The analysis identifies three prominent frames found in Latvian media: (i) a biomedical frame, (ii) a psychological frame, and (iii) a social practice frame. The frames are connected by several cross-cutting themes: individualisation, self-disciplining, gendering, and medicalisation. The results suggest that the media portray unhealthy dietary as the responsibility of individuals, whilst ignoring, with some exceptions, the impact of broader societal and food system processes. These results call for more attention to be paid by media content creators to the diversity of actors involved in food production, consumption and distribution and their inter-connections, as well as the impact that food systems have on economic, social, and ecological sustainability.